Cooking and electronic cigarettes leading to large differences between indoor and outdoor particle composition and concentration measured by aerosol mass spectrometry. Issue 6 (15th May 2020) - Omelekhina, Yuliya; Eriksson, Axel; Canonaco, Francesco; Prevot, Andre S. H.; Nilsson, Patrik; Isaxon, Christina; Pagels, Joakim; Wierzbicka, Aneta
Abstract : This study assesses aerosol chemical composition PM1 (<1 μm) with the state-of-the-art techniques inside and outside of an occupied residence. Abstract : We spend about two thirds of our time in private homes where airborne particles of indoor and outdoor origins are present. The negative health effects of exposure to outdoor particles are known. The characteristics of indoor airborne particles, though, are not well understood. This study assesses the differences in chemical composition of PM1 (<1 μm) inside and outside of an occupied Swedish residence in real time with a High-Resolution Time-of-Flight Aerosol Mass Spectrometer (HR-ToF-AMS) and an Aethalometer. The chemical composition and concentration of particles indoors showed large differences compared to outdoors. The average indoor concentration was 15 μg m −3 and was higher than the outdoor 7 μg m −3 . Organics dominated indoor particle composition (86% of the total mass) and originated from indoor sources (cooking, e-cigarette vaping). The average indoor to outdoor ratios were 5.5 for organic matter, 1.0 for black carbon, 0.6 for sulphate, 0.1 for nitrate, 0.2 for ammonium and 0.2 for chloride. The occupancy time accounted for 97% of the total measured period. Four factors were identified in the source apportionment of organic particle fraction by applying positive matrix factorization (PMF): two cooking factors, one e-cigarette factor and one outdoor contribution (OOA) organic factor penetrated from outside.